2023
DOI: 10.3390/ijms24054351
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood-Derived Cell Therapy for Perinatal Brain Injury: A Systematic Review & Meta-Analysis of Preclinical Studies

Abstract: Perinatal brain injury is a major contributor to long-term adverse neurodevelopment. There is mounting preclinical evidence for use of umbilical cord blood (UCB)-derived cell therapy as potential treatment. To systematically review and analyse effects of UCB-derived cell therapy on brain outcomes in preclinical models of perinatal brain injury. MEDLINE and Embase databases were searched for relevant studies. Brain injury outcomes were extracted for meta-analysis to calculate standard mean difference (SMD) with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…On the basis of our findings in preterm sheep, we suggest that caution should be taken in future studies if UCB cells are to be used in preterm infants as an early therapeutic intervention strategy for preterm brain injury. The growing interest in, feasibility and safety profile of UCB cells for preterm infants encourages their early administration to optimise neuroprotection [ 4 , 9 , 48 , 49 ], however in these studies “early” treatment is still > 12 h post initial insult. Notwithstanding the other morbidities that are likely to occur in preterm infants, the majority of preterm infants require respiratory support for varying periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our findings in preterm sheep, we suggest that caution should be taken in future studies if UCB cells are to be used in preterm infants as an early therapeutic intervention strategy for preterm brain injury. The growing interest in, feasibility and safety profile of UCB cells for preterm infants encourages their early administration to optimise neuroprotection [ 4 , 9 , 48 , 49 ], however in these studies “early” treatment is still > 12 h post initial insult. Notwithstanding the other morbidities that are likely to occur in preterm infants, the majority of preterm infants require respiratory support for varying periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic meta-analysis of 55 studies demonstrated that UCB-derived cell therapy was an efficacious treatment in pre-clinical models of perinatal brain injury. 55 UCB-derived cells were thought to exert their neuroprotective effects by significantly reducing microglial activation, astrogliosis, apoptosis, neuroinflammation and so reducing infarct size, and improving numbers of neurons and oligodendrocytes and overall motor function. Further analysis suggested that these therapies may be more efficacious in IVH models compared to models of hypoxia ischemia and when given through local routes as compared to systemic routes.…”
Section: Cord Blood-derived Cell Therapiesmentioning
confidence: 99%
“…One of the most studied sources of cells for treating neonatal brain disorders is the umbilical cord blood, which contains hematopoietic stem/progenitor cells, endothelial progenitor cells, monocytes, mesenchymal stem cells, and lymphocytes, among other circulating mononuclear cells. Multiple studies have demonstrated that umbilical cord blood cells protect the brain in HIE and NAIS 123–126 …”
Section: Potential Treatments For Hie and Nais Focused On Monocytesmentioning
confidence: 99%
“…Multiple studies have demonstrated that umbilical cord blood cells protect the brain in HIE and NAIS. [123][124][125][126] Currently, it is unknown which cell types present in the umbilical cord blood are necessary for the beneficial effects observed in these models. Saha et al 127 demonstrated that CD14 + monocytes from the umbilical cord blood protected neurons and reduced glial activation in organotypic forebrain slice cultures subjected to oxygen-glucose deprivation.…”
Section: Cell-based Therapiesmentioning
confidence: 99%